2000
DOI: 10.1046/j.1469-8137.2000.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of molecular genetic variation in Plantago major and P. intermedia in relation to ozone resistance

Abstract: Patterns of molecular genetic variation were examined in seed collections of Plantago major and Plantago intermedia, used previously to investigate the variations in ozone (O $ ) resistance of these species across Europe. Total genomic DNA was amplified with random primers (random amplied polymorphic DNA (RAPD) and intersingle sequence repeats (SSR)) to produce 73 genetic markers. In addition, allozyme and chloroplast variations were surveyed. Genetic markers were examined for association with O $ resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Two sub-species of P. major were also differentiated using RAPD and ISSR markers (Wolff and Morgan-Richards 1998). Simultaneously, Wolff et al (2000) studied the patterns of molecular genetic variation in P. major and P. intermedia in relation to ozone resistance. A molecular relationship of the seven species showed that P. arenaria and P. psyllium formed a most closely related group followed by the second closely related group of P. serraria and P. coronopus.…”
Section: Resultsmentioning
confidence: 99%
“…Two sub-species of P. major were also differentiated using RAPD and ISSR markers (Wolff and Morgan-Richards 1998). Simultaneously, Wolff et al (2000) studied the patterns of molecular genetic variation in P. major and P. intermedia in relation to ozone resistance. A molecular relationship of the seven species showed that P. arenaria and P. psyllium formed a most closely related group followed by the second closely related group of P. serraria and P. coronopus.…”
Section: Resultsmentioning
confidence: 99%
“…Using random amplified polymorphic DNA primers, the latter populations were subsets of the earlier ones, supporting in situ evolution, rather than catastrophic loss and replacement of the populations (Wolff et al . ).…”
Section: Physiological Effectsmentioning
confidence: 97%
“…The research team concluded that the observed change in population O 3 tolerance was due to differential selection of genotypes already present, rather than through an influx of new English plantain germplasm (Wolff et al . ).…”
Section: Case Studiesmentioning
confidence: 99%
“…Similarly, Vahabi et al used molecular and morphological markers for the evaluation of genetic diversity between P. ovate (Vahabi et al 2008). Wolff and Morgan-Richards used random amplified polymorphic DNA (RAPD) markers for differentiating subspecies of Plantago major (Wolff et al 2000). Samantaray et al used RAPD markers to assess genetic relationships and variance in seven species of Plantago, i.e., P. ovata (Forsk.…”
Section: Preserving Genetic Integritymentioning
confidence: 99%